Case Report: Cardiac Toxicity Associated With Immune Checkpoint Inhibitors - Chen, Ru; Peng, Ling; Qiu, Zhihua; Wang, Yan; Wei, Fen; Zhou, Min; Zhu, Feng (Frontiers in Cardiovascular Medicine, 2021)
Immune checkpoint inhibitors (ICIs) have now emerged as a mainstay of treatment for various cancer. Along with the development of ICIs, immune-related adverse effects (irAEs) have been the subject of wide attention. The cardiac irAE, a rare but potentially fatal and fulminant effect, have been reported recently. This article retrospectively reviewed 10 cases from our hospital with cardiac irAEs, with severity ranging from asymptomatic troponin-I elevations to cardiac conduction abnormalities and even fulminant myocarditis. In our series, all the cases were solid tumors and lung cancer was the most frequent cancer type (4,40%). In total, three (30.0%) patients experienced more than one type of life-threatening complication. A systemic corticosteroid was given to nine patients (90.0%). The majority of cases (7, 70%) were performed at an initial dose of 1–2 mg/kg/day. Two (20.0%) patients were admitted to ICU, three (30.0%) patients were put on mechanical ventilation, two (20.0%) patients received the plasma exchange therapy, and one patient was implanted with a pacemaker. Two (20.0%) of the patients succumbed and died, with a median duration of 7.5 days (IQR5.0–10.0) from diagnosis of cardiac irAE to death. Based on these results, we recommend that clinicians be alert to cardiac irAEs, including performing cardiovascular examinations before ICI treatment to accurately diagnose suspected myocarditis, enabling immediate initiation of immunosuppressive therapy to improve prognosis.